2022
DOI: 10.3390/jpm12040512
|View full text |Cite
|
Sign up to set email alerts
|

Promising Effects of Digital Chest Tube Drainage System for Pulmonary Resection: A Systematic Review and Network Meta-Analysis

Abstract: Objective: The chest tube drainage system (CTDS) of choice for the pleural cavity after pulmonary resection remains controversial. This systematic review and network meta-analysis (NMA) aimed to assess the length of hospital stay, chest tube placement duration, and prolonged air leak among different types of CTDS. Methods: This systemic review and NMA included 21 randomized controlled trials (3399 patients) in PubMed and Embase until 1 June 2021. We performed a frequentist random effect in our NMA, and a P-sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In addition to the systems used in this study, there are now digital systems that enable a numerical and objective evaluation of the air leak flow and the amount of liquid withdrawn. 17 These tend to be lighter than the common water-seal system; however, these are not emptiable, and their standard reception canister has a maximum volume of 800 mL. In addition, these require a non-disposable electronic pump for functioning, which costs approximately US$ 4,000.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the systems used in this study, there are now digital systems that enable a numerical and objective evaluation of the air leak flow and the amount of liquid withdrawn. 17 These tend to be lighter than the common water-seal system; however, these are not emptiable, and their standard reception canister has a maximum volume of 800 mL. In addition, these require a non-disposable electronic pump for functioning, which costs approximately US$ 4,000.…”
Section: Discussionmentioning
confidence: 99%
“…Since this trial, more studies have been published and recently, Chang et al released a meta-analysis ( 2 ), in which they observed a 1.4 days diminution for length of hospital stay and a reduced chest tube duration of 0,68 days with digital drainage system use.…”
mentioning
confidence: 99%